FACTORS THAT IMPACT STUDENTS’ SATISFACTION WITH MEDICAL CARE AT THE NAZARBAYEV UNIVERSITY HEALTH CENTER - Zhumanov, Kanat; Kyzyrbayeva, Dinara; Sadvakassov, Askar (Nazarbayev University Graduate School of Public Policy, 2024)
The objective of this research is to identify and assess the factors affecting students’ overall satisfaction with the quality of healthcare services provided by the UHC at Nazarbayev University. NU1 is widely recognized as one of the leading higher education institutions in Central Asia and it has its own medical center - UHC, which was established in 2018. UHC has since focused on achieving high standards in its services to meet the healthcare needs of NU’s growing student and staff population. The UHC employs 65 staff members, including both healthcare specialists and administrative personnel.
Keywords: Type of access: Open; healthcare services; UHC; Nazarbayev University